2002
DOI: 10.1177/1354067x02008001625
|View full text |Cite
|
Sign up to set email alerts
|

Rewriting Memories: Family Recollections of the National Socialist Past in Germany

Abstract: This article deals with the question of how personal memories of the national socialist past in Germany are passed on to younger generations. Rather than viewing this process as an unidirectional handing down of memories from generation to generation, examination is made of how memories are negotiated and re-created in intergenerational discourse. Drawing on a series of case studies, there is discussion of how the meaning of past experiences is construed and organized within particular narrative genres. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
(11 reference statements)
2
33
0
1
Order By: Relevance
“…This sometimes resulted in a greater critical Further, by explicitly examining the intersections of the institutionalized and the (noninstitutionalized) individual memories, the Model can reveal some mechanisms of "resistance" or reinterpretations of the "official" memories (Popular Memory Group 2011[1982). Specifically, in this research it demonstrated the importance of the interactional level of mnemonic communities (such as family) as alternative sources of presentations of the past (Beim 2007;Fine and Beim 2007;Tschuggnall and Welzer 2002;Welzer 2010;Clarke and Wölfel 2011), as well as the relevance of socio-cultural experiences which filter the salience and resonance of all available presentations of the past (Griswold 1987b;Zerubavel 1997;Radway 1984;Zelizer 1993). Finally, this Model can also be used as a starting point of more in-depth explorations of other mechanisms which affect the credibility and differential use of available presentations of the past, such as the educational effect or credibility of the form in which the past is presented.…”
Section: The Main Findings and Interactional Model Of Collective Memomentioning
confidence: 99%
See 4 more Smart Citations
“…This sometimes resulted in a greater critical Further, by explicitly examining the intersections of the institutionalized and the (noninstitutionalized) individual memories, the Model can reveal some mechanisms of "resistance" or reinterpretations of the "official" memories (Popular Memory Group 2011[1982). Specifically, in this research it demonstrated the importance of the interactional level of mnemonic communities (such as family) as alternative sources of presentations of the past (Beim 2007;Fine and Beim 2007;Tschuggnall and Welzer 2002;Welzer 2010;Clarke and Wölfel 2011), as well as the relevance of socio-cultural experiences which filter the salience and resonance of all available presentations of the past (Griswold 1987b;Zerubavel 1997;Radway 1984;Zelizer 1993). Finally, this Model can also be used as a starting point of more in-depth explorations of other mechanisms which affect the credibility and differential use of available presentations of the past, such as the educational effect or credibility of the form in which the past is presented.…”
Section: The Main Findings and Interactional Model Of Collective Memomentioning
confidence: 99%
“…Young generations, thus, reinterpreted their grandparents' stories by ignoring all "problematic" elements and even re-inventing their grandparents' behavior in ways that fit with young people's values based on their internalized negative evaluations of the Holocaust and the German Nazi past (Tschuggnall and Welzer 2002;Welzer 2008Welzer , 2010Welzer , 2011. Therefore, this research highlighted that family talk is an important and trusted source not only in the cases where it provides alternative narratives to those dis-trusted state ones, as in Wertsch's example above, but also in cases where official narratives are accepted and internalized.…”
Section: Competing Sources Of Repertoires Of Collective Memoriesmentioning
confidence: 99%
See 3 more Smart Citations